Lower soluble Klotho levels in the pretransplant period are associated with an increased risk of renal function decline in renal transplant patients. Issue 3 (21st September 2020) - Shikida, Yasuto; Mizobuchi, Masahide; Yoshitake, Osamu; Kato, Tadashi; Ogata, Hiroaki; Koiwa, Fumihiko; Honda, Hirokazu
Abstract: Serum soluble Klotho levels are associated with renal function in predialysis patients with chronic kidney disease. However, few reports exist regarding the association between soluble Klotho levels and renal function in kidney transplant (KTx) recipients. This was a retrospective observational study of 41 living KTx recipients. The serum soluble Klotho levels were classed as "high" (>456 pg/mL [i.e., high‐Klotho group]) or "low" (≤456 pg/mL [i.e., low‐Klotho group]). Renal function decline was defined as a decrease in the estimated glomerular filtration rate (eGFR) of 30% or more from the baseline value within 3 months after KTx. A multivariable time‐to‐event analysis between the groups was conducted. Among the KTx recipients, the incidence of a 30% decrease in the eGFR was significantly higher in the low‐Klotho group than in the high‐Klotho group ( P = .036). After adjusting for donor age, donor sex, the presence of rejection, and the number of cytomegalovirus infections, multivariable Cox models revealed that low soluble Klotho levels remained associated with a higher risk of a 30% decrease in the eGFR (hazard ratio, 2.38; 95% confidence interval, 1.02‐6.41). These findings suggested that lower soluble Klotho levels in the pre‐KTx period are associated with an increased risk of renal function decline in KTx recipients.